Evaluation of Multiple Linear Regression–Based Limited Sampling Strategies for Enteric-Coated Mycophenolate Sodium in Adult Kidney Transplant Recipients. Issue 2 (April 2018) - Brooks, Emily K.; Tett, Susan E.; Isbel, Nicole M.; McWhinney, Brett; Staatz, Christine E.
Abstract : Background: Although multiple linear regression–based limited sampling strategies (LSSs) have been published for enteric-coated mycophenolate sodium, none have been evaluated for the prediction of subsequent mycophenolic acid (MPA) exposure. This study aimed to examine the predictive performance of the published LSS for the estimation of future MPA area under the concentration–time curve from 0 to 12 hours (AUC0–12 ) in renal transplant recipients. Methods: Total MPA plasma concentrations were measured in 20 adult renal transplant patients on 2 occasions a week apart. All subjects received concomitant tacrolimus and were approximately 1 month after transplant. Samples were taken at 0, 0.33, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 6, and 8 hours and 0, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 2, 3, 4, 6, 9, and 12 hours after dose on the first and second sampling occasion, respectively. Predicted MPA AUC0–12 was calculated using 19 published LSSs and data from the first or second sampling occasion for each patient and compared with the second occasion full MPA AUC0–12 calculated using the linear trapezoidal rule. Bias (median percentage prediction error) and imprecision (median absolute prediction error) were determined. Results: Median percentage prediction error and median absolute prediction error for the prediction of full MPA AUC0–12 were <15% for 4 LSSs, using the data from the same (second) occasion. One equation (1.583C1 + 0.765C2 + 0.369C2.5 + 0.748C3 + 1.518C4 + 2.158C6 + 3.292C8 + 3.6690) showed bias and imprecision <15% for the prediction of future MPA AUC0–12, where the predicted AUC0–12 from the first occasion was compared with the full AUC0–12 from the second. All LSSs with an acceptable predictive performance included concentrations taken at least 6 hours after the dose. Conclusions: Only one LSS had an acceptable bias and precision for future estimation. Accurate dosage prediction using a multiple linear regression–based LSS was not possible without concentrations up to at least 8 hours after the dose. Abstract : Supplemental Digital Content is Available in the Text.